PUSTAKAWAN SEBAGAI PELAYANAN INFORMASI BAGI PEMUSTAKA - Armen Armen (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2018)
Abstract: To meet the information needs for users who are fast, precise, and accurate, they need Professional Librarians, who are trained and have expertise and have a sense of responsibility (as information processors). Without mastering information technology, the Librarian will miss information, because information always changes every time, even every second. Information becomes a basic need for certain users, so that if the information needs are not met will be a problem for users. Information needed by visitors aims to increase knowledge and improve skills which can ultimately change mindsets (Mindset). In this information age which is very competitive, information becomes very important for Librarians and Librarians in a sustainable manner to deepen knowledge.Keywords: Librarians as Information ManagersAbstrak : Untuk memenuhi kebutuhan informasi bagi Pemustaka yang cepat tepat dan akurat dibutuhkan Pustakawan yang Profesional, terlatih dan punya keahlian dan memiliki rasa tanggung jawab (sebagai pengelolah informasi). Tanpa menguasai teknologi informasi maka Pustakawan akan ketinggalan informasi, karena informasi selalu berubah setiap waktu bahkan setiap detik. Informasi menjadi kebutuhan pokok bagi pengguna tertentu, sehingga jika kebutuhan informasinya tidak terpenuhi akan menjadi masalah bagi pemustaka. Informasi dibutuhkan pemustaka bertujuan untuk menambah pengetahuan dan meningkatkan keterampilan yang pada akhirnya dapat merubah pola pikir (Mindset). Dalam Era informasi ini yang sangat kompetitif ini, informasi menjadi sangat penting bagi Pustakawan dan Pemustaka secara berkelanjutan untuk memperdalam ilmu pengetahuan.Kata kunci : Pustakawan Sebagai Pengelola Informasi